Developmental changes in erythrocyte Na+, K+-ATPase subunit abundance and enzyme activity in neonates. Issue 2 (1st September 2000) - Vasarhelyi, Barna; Tulassay, Tivadar; Ver, Agota; Dobos, Mariann; Kocsis, Istvan; Seri, Istvan
Abstract : AIM: To study the relation between erythrocyte Na +, K + -ATPase subunit isoform composition, Na +, K + -ATPase activity, and cation pump function in preterm and term neonates. DESIGN: Erythrocyte Na +, K + -ATPase subunit isoform abundance, Na +, K + -ATPase activity, and cation pump function were studied in blood samples obtained from 56 preterm neonates of 28–32 weeks gestation (group 1), 58 preterm neonates of 33–36 weeks gestation (group 2), and 122 term neonates (group 3) during the first two postnatal days. RESULTS: α1 isoform abundance was higher and β2 isoform abundance was lower in group 1 than in group 3 (p = 0.0002). α2 and β1 isoform abundance did not change with maturation and there was no evidence for the presence of the α3 isoform. Gestational age was inversely related to Na +, K + -ATPase activity (p = 0.0001) and directly related to intracellular Na + concentration (p = 0.0025). CONCLUSIONS: Expression of the α1 and β2 Na +, K + -ATPase subunit isoforms is developmentally regulated. The increased abundance of α1 isoforms of immature neonates translates to increased ATPase activity. The lower intracellular Na + concentration of immature neonates suggests that their erythrocyte Na +, K + -ATPase cation pump function may also be increased.